RECOGNIZING ILLOCUTIONARY SPEECH ACTS AND SOCIAL INTERACTIONS IN AMY TAN'S BONESETTER DAUGHTER NOVEL THROUGH SOCIO-PRAGMATIC ANALYSIS (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Language is a powerful tool for expressing identity, navigating relationships, and addressing cultural complexities, particularly in literary works that explore intricate social dynamics. This study investigates the interplay between language, cultural context, and communication within Amy Tan’s The Bonesetter’s Daughter, emphasizing how speech acts reflect and navigate complex social relationships. Through a socio-pragmatic framework, the research examines dialogues and interactions in the novel to identify illocutionary speech acts and their socio-cultural implications. Utilizing text and content analysis methods, data were collected using the AntConc tool to identify keywords associated with various speech acts, followed by a detailed analysis of the characters' utterances. The findings reveal 499 instances of illocutionary speech acts, categorized into assertive, directive, expressive, commissive, and declarative types as outlined by Searle’s theory. These acts illustrate the characters' efforts to navigate cultural conflicts, identity struggles, and generational tensions, particularly within the mother-daughter dynamic between Ruth and LuLing. The study underscores the role of language in mediating relationships, resolving conflicts, and expressing cultural identity. By providing insights into how speech acts operate within specific social and cultural contexts, this research contributes to the fields of sociolinguistics and literary studies. It highlights the practical application of socio-pragmatic analysis in understanding the relationship between language, culture, and identity in literature.